PENGARUH UKURAN BIJI JARAK PAGAR TERHADAP LAMANYA NYALA API DAN TEMPERATUR YANG DIHASILKAN PADA KOMPOR - Mila, Andika Nopriansyah; Junaidi, Ahmad; Arnoldi, Dwi; Witjahjo, Soegeng; Hidayati, Baiti; Rizal, Syamsul; Medi, Ali (MACHINERY Jurnal Teknologi Terapan, 2023)
The availability of fuels, especially fossil fuels, is increasingly scarce, concerns about meeting energy needs in the future are increasing. In urban areas, fuel gas (LPG) is generally used for daily cooking, while in rural areas, kerosene is more commonly used. This significant oil content opens up the possibility to use castor beans as fuel directly. Therefore, in this study the author conducted an experiment entitled "The Effect of Jatropha Bean Size on Fire Intensity and Temperature produced on the Stove". The variable used is jatropha beans weighing 350 grams in each form of castor bean roughness, namely: whole, peeled, coarse and fine. Where the results obtained from the research that has been carried out are whole castor beans with a flame for 93 minutes and a temperature of 314.7 °C, peeled to produce a flame for 85 minutes and a temperature of 433.3 °C, coarsely crushed to produce a flame for 73 minutes and a temperature of 498.8 °C, and finely crushed to produce a flame of 65 minutes and a temperature of 519 °C. So it can be concluded from the data produced, the larger the size of the castor bean, the more time the fire is and the finer the roughness of the castor bean fence, the higher the resulting temperature.